Projecting India in Chinese Medieval Buddhist sources: a case of Sinizication? - Deeg, Max (Studies in Chinese Religions, 2024)
Following the ‘Call for Proposals’ suggestive ‘multi-layered contextualization approach,’ this article will revisit the concept of Sinicization of Buddhism from a more general and theoretical viewpoint. Having approached the concept from a more theoretical point of view, the Sinicization paradigm as a hermeneutical tool to understand processes and developments in Chinese Buddhism will then be tested against some specific cases of practice-related discourses in Buddhist circles of the early Tang period.